Sensory and Chemical Properties of Virginia Hard Cider: Effects of Apple Cultivar Selection and Fermentation Strategy. (2nd January 2023) - Littleson, Brenna; Chang, Elizabeth; Neill, Clinton; Phetxumphou, Katherine; Sandbrook, Ann; Stewart, Amanda; Lahne, Jacob
Abstract: The U.S. cider market has expanded in recent years, but limited research-based information is available on fermentation management. This study investigates how apple cultivar and yeast inoculation affect the chemical and sensory properties of ciders made in Virginia. Four ciders were produced in triplicate using combinations of two different apple cultivars — Harrison, a cider cultivar and GoldRush, a dessert cultivar — and two fermentation strategies — inoculated with dry active yeast EC1118 or Pied de Cuvé (PdC) ambient fermentation. Ciders were analyzed for alcohol content, free/total SO2, titratable acidity, volatile acidity, malic acid, pH, and residual sugar. Sensory evaluation was conducted using descriptive analysis with trained panelists. Results were analyzed via analysis of variance (ANOVA) and principal component analysis. Apple cultivar and fermentation method resulted in significant differences for chemistry and sensory parameters. Malic acid concentration was greater in the control ciders while concentrations of both residual sugar and volatile acidity were higher in the PdC ciders. The interaction effect of cultivar*fermentation method influenced both malic acid and residual sugar concentrations, where concentration differences between control and ambient ciders were smaller for GoldRush than for Harrison, showing that fermentation style produced different results across cultivars. Volatile acidity produced opposite interaction effects as differences between fermentation styles were larger for GoldRush. For sensory attributes, Harrison ciders produced high intensities for multiple attributes, but also higher variability. Multiple sensory descriptors displayed interaction effects as the fermentation method produced different results in different cultivars. This study demonstrates that increasingly popular practices in the industry can produce significantly different ciders.